Oil palm biomass as a resource for sustainable production of cellulose nanofiber - Ariffin, Hidayah; Tengku Yasim Anuar, Tengku Arisyah; Norrrahim, Mohd Nor Faiz; Shirai, Yoshihito; Nishida, Haruo; Ando, Yoshito; Hassan, Mohd Ali (2018)
In this study, cellulose nanofiber (CNF) was produced from oil palm biomass (OPB) by using a wet disk mill (WDM). It was exhibited that the produced CNF had diameter in the range of 10-30 nm. When blended with low density polyethylene (LDPE) at 3 wt% CNF, the biocomposites resulted in an increment in tensile strength and flexural strength by 55% and 195% as compared to neat LDPE. Despite of the CNF ability to improve mechanical properties of the biocomposites, the CNF production suffers in term of high energy requirement due to the intense mechanical processing. Herewith, it is suggested that a sustainable production of CNF from OPB can be achieved by coupling the process with palm oil processing which is currently generating excess steam energy equivalent to 3.64 GW h/y, to create an overall palm oil mill biorefinery which includes material production.